Operation of Residential Irrigation Controllers - Michael D. Dukes; Dorota Z. Haman (EDIS)
Automatic landscape irrigation systems have become quite common in Florida in recent years. Electronic irrigation controllers are used to control these systems; however, it is not always obvious how to program these controllers to apply the desired amount of irrigation water. This document is CIR1421, one of a series of the Agricultural and Biological Engineering Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First published July 2002.